2018
DOI: 10.1259/bjr.20170731
|View full text |Cite
|
Sign up to set email alerts
|

Perceived patient burden and acceptability of whole body MRI for staging lung and colorectal cancer; comparison with standard staging investigations

Abstract: WB-MRI is marginally less acceptable and more burdensome than standard scans, particularly for patients with pre-existing distress and comorbidities.  Advances in knowledge: This research shows that WB-MRI scan burden, although low, is higher than for current staging modalities among patients with suspected colorectal or lung cancer. Psychological and physical comorbidities adversely impact on patient experience of WB-MRI. Patients with high distress or comorbid illness may need additional support to undergo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…The results of these studies have been published elsewhere. 6,17,18 The present study uses some of the questionnaire data published previously 17 and reports a secondary analysis, the association with scan quality. The full recruitment pathway and reasons for exclusion are given in Fig 1. In detail, consenting patients were mailed a baseline questionnaire within 1e2 days of trial registration, which they returned using a stamped addressed reply envelope.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies have been published elsewhere. 6,17,18 The present study uses some of the questionnaire data published previously 17 and reports a secondary analysis, the association with scan quality. The full recruitment pathway and reasons for exclusion are given in Fig 1. In detail, consenting patients were mailed a baseline questionnaire within 1e2 days of trial registration, which they returned using a stamped addressed reply envelope.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The original questionnaire study was powered to assess whether WB-MRI posed a greater burden on patients than standard staging pathways. 17 Baseline questionnaire content Demographics Age, gender, and ethnicity were captured in the questionnaire but missing data on age and gender was supplied via the central trial database (with patient consent). Postcode data, also supplied by the central trial database, was used to calculate an area based deprivation score for each individual using the 2010 English Indices of Deprivation scale, 19 categorised into quintiles from 1 (highest levels of deprivation) to 5 (lowest).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…80 Participant experience during WB-MRI is variable, but most employ some form of coping strategy and complete the scan. Study 2 34 built on the findings of study 1, which suggested that for some participants WB-MRI is a greater challenge than standard staging scans. We quantified participant experiences during staging pathways using questionnaires and in particular compared WB-MRI with CT (Streamline C participants) and with PET-CT (Streamline L participants).…”
Section: Participant Experiencementioning
confidence: 99%
“…Includes minor additions and formatting changes to the original text. 34 This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: http://creativecommons.org/licenses/by/4.0/.…”
Section: University Hospital Southampton Nhs Foundation Trustmentioning
confidence: 99%
See 1 more Smart Citation